American youth cultures - Campbell, Neil, 1957- (Edinburgh University Press, 2004)
Surfing, punk rock, Dawson's Creek, teen movies, MTV and S.E. Hinton's The Outsiders are among the many popular cultural landmarks examined in American Youth Cultures. It considers themes such as race, class, gender, power, sexuality and authority and presents innovative and challenging analyses of texts from the post-war period. Key questions are raised about the significance of youth within American culture. Contributing to the necessary and important debate over the meanings of youth representation within American culture, the ideological nature of youth and its centrality to a complex reading of popular culture are emphasised. In particular the issues of gender, race and sexuality are considered as central to the construction of youth identity and to other significant relationships between youth and authority. The contradictions in youth representation are asserted, denying any easy definitions that might serve to compound stereotypes or sustain vested interests. The authors show how the cultural politics of youth are no longer only about being young but rather associated with both personal and public values, aspirations and ideologies that extend way beyond any simple consideration of the self. Key Features: * The only available book on the subject * Youth is shown to be central to contemporary American culture * Contributors bring a range of approaches to bear on representations of youth in American culture.